2009
DOI: 10.1007/s11192-009-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Can the centre–periphery model explain patterns of international scientific collaboration among threshold and industrialised countries? The case of South Africa and Germany

Abstract: As scientific collaboration is a phenomenon that is becoming increasingly important, studies on scientific collaboration are numerous. Despite the proliferation of studies on various dimensions of collaboration, there is still a dearth of analyses on the effects, motives and modes of collaboration in the context of developing countries. Adopting Wallerstein's world-system theory, this paper makes use of bibliometric data in an attempt to understand the pattern of collaboration that emerges between South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 29 publications
(23 reference statements)
0
48
0
1
Order By: Relevance
“…Differences in economic resources among geographic areas (economic distance) may determine the spatial patterns in SC, as derived from the centre-periphery hypothesis (Schott, 1998;Schubert and Sooryamoorthy, 2010) applied to research collaboration (Acosta et al, 2011a). According to this literature, scientists in peripheral countries are willing to collaborate with core countries to gain access to resources, while core areas seeking complementarities (Hwang, 2008;Sonnenwald, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Differences in economic resources among geographic areas (economic distance) may determine the spatial patterns in SC, as derived from the centre-periphery hypothesis (Schott, 1998;Schubert and Sooryamoorthy, 2010) applied to research collaboration (Acosta et al, 2011a). According to this literature, scientists in peripheral countries are willing to collaborate with core countries to gain access to resources, while core areas seeking complementarities (Hwang, 2008;Sonnenwald, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We need to turn to the international literature on collaboration to find suitable references. In this regard, the centre-periphery discussion at the international level (Schott, 1998;Schubert and Sooryamoorthy, 2010) provides some clues on whether differences in economic development between areas may determine the patterns of scientific collaboration.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…Researchers collaborate with each other for various reasons. This can be to improve their visibility and recognition (Narin et al 1991), to utilise expensive equipment that is not under their control (Meadows and O'Connor 1971;Schubert and Sooryamoorthy 2010), or to acquire expertise and new ideas (Beaver and Rosen 1978) needed for research.…”
Section: Introductionmentioning
confidence: 99%
“…Onyancha and Maluleka (2011) found out that knowledge production through collaborative research among sub-Saharan African countries is minimal. Schubert and Sooryamoorthy (2010) showed that "a theory of scientific collaboration building on the notion of marginality and centre-periphery can explain many facets of South African-German collaboration, where South Africa is a semi-peripheral region, a centre for the periphery, and a periphery for the centre".…”
Section: Introductionmentioning
confidence: 99%